PERSEPSI ELIT LOKAL TERHADAP WACANA PEMEKARAN DAERAH DI KABUPATEN CILACAP - Yuwanto Yuwanto (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
Indonesia’s 2001 decentralization was a “Big Bang,” indeed. It promised to fundamentally change the locus of responsibility and accountability for public service delivery in Indonesia. By “bringing government closer to the people,” decentralization can serve as a driving force towards generating improvements in Indonesia’s notably poor governance environment. Increasingly, regional autonomy was considered to be, and presented as the natural complement to the emerging democracy at the central level. In such of this circumstances, the idea and discourse about region splitting (pemekaran daerah) emerged intensively. In addressing these issues, the government needs to carefully balance its desire to maintain a unitary state with the aspirations of the regions, and the opportunities offered by a more decentralized system of government. Keywords: decentralisation, local elite, region splitting